Therapy of chronic hepatitis C virus infection in HIV co-infected people. - Fabris, P; Barnes, E; Tositti, G; Giordani, M; Grasso, A; De Lalla, F (2004)
The introduction of highly active anti-retroviral therapy (HAART) for Human Immunodeficiency Virus (HIV) infection has significantly improved the life expectancy of HIV positive patients. Hepatitis C virus (HCV) co-infection is common in HIV infected patients and is now a significant cause of morbidity and mortality. Optimal management and treatment of HCV in HIV infected patients is therefore essential. Interferon-alpha (IFN-alpha) and ribavirin is the mainstay of treatment for HCV infection in HIV infected people. The sustained virological response rate (SVR) with combination therapy is lower than that commonly observed in HCV mono-infected patients. This is, at least in part, due to the very high treatment drop out rates. Ribavirin in combination with HAART is associated with particular side effects such as mitochondrial toxicity. Therefore, vigilant monitoring of patients during therapy, in specialist centers is essential. Pegylated interferon (PEG-IFN) plus ribavirin is particularly promising as it is easier to administer and will probably become the treatment of choice for co-infected patients. A SVR is associated with genotype 2 and 3, in addition to a high CD4+ cell count and a low HCV load prior to therapy. The progression of HCV related liver disease in HIV positive patients is faster than in subjects with HCV infection alone. As a result, there is an increasing incidence of cirrhosis and end-stage liver disease in co-infected patients. Liver transplantation is being evaluated in many centers. To date the experiences are very limited but encouraging in term of survival rate.